Rheological quantification of aging, rejuvenation and modification in bitumen - Peralta, J. (2011)
The transport infrastructures, namely the highways, play a key role in the development of modern economies. However, roads are not eternal and need periodic rehabilitations. These works affect the traffic and carry on huge user costs. One of the factors that reduce pavement life is the binder (bitumen) aging, since the aged bitumen became stiffer, thus reducing the fatigue cracking resistance of the pavement. We recently proposed a new rheological parameter to quantify bitumen aging. This parameter performed better than parameters used in standard testing of bitumen [1]. The addition of crump rubber from used tires to bitumen is a new route to the improvement of pavement. Such bitumen modification was also studied using a new “sphere asphalt rubber production simulator” and the new rheological parameter designed for the quantification of aging. Bitumen recycled from pavements also needs to be modified through the addition of rejuvenating agents in order to be re-used. The impact of different commercial additives on the bitumen rheological properties is presently explored. This line of research is highly multidisciplinary as material scientists, chemists, and civil engineers are involved in the research team. However, dedicated techniques for the structural characterization of these complex materials at different length scales are highly needed, together with some theoretical alternative to existing colloidal models.